Integrasi Teori Gaya Belajar Barat dan Perspektif Islam dalam Proses Pembelajaran - Kurnia Tri Puspita; Mu’alimin Mu’alimin; Mukaffan Mukaffan (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
Learning style theories have long been used to understand individual differences in learning processes. Models such as VAK (Visual, Auditory, Kinesthetic) and Multiple Intelligences offer frameworks for adapting instructional strategies to students’ preferences. However, these approaches have been criticized for their reductionism and limited empirical validity, often neglecting the holistic nature of human learning. In contrast, the Islamic concept of fitrah provides a more comprehensive perspective, encompassing intellectual, spiritual, moral, and emotional dimensions in an integrated manner. This conceptual article aims to analyze and integrate Western learning style theories with Islamic perspectives to develop a more holistic learning paradigm. Through an extensive literature review and theoretical analysis, the article proposes an integrative model that bridges empirical approaches with spiritual values. Theoretically, this integration enriches academic discourse by connecting two distinct knowledge traditions. Practically, it offers a framework for educators and institutions to design adaptive learning processes that address learner diversity while fostering spiritual and moral development.